REGULA FORENSICS FACE SDK SEBAGAI SISTEM ABSENSI BERBASIS PENGENALAN WAJAH PADA PLATFORM ANDROID - Widjaya, Rendi; Irwansyah, Irwansyah; Rizal, Rizal; Budiyantara, Agus; M, Tupan Tri (Infotech: Journal of Technology Information, 2025)
Attendance is one of the important activities in organizational management, especially in the fields of education and business. Until now, attendance systems are still mostly done manually with signatures or ID cards. However, these methods are prone to fraud, such as buddy punching or data manipulation. This study aims to develop a facial recognition-based attendance system on the Android platform using Regula Forensics Face SDK. Test results at thresholds of 70%, 85%, and 90% show that the 85% threshold provides the best compromise, with a False Acceptance Rate (FAR) of 0% and a False Rejection Rate (FRR) of 14.3%. In conclusion, a facial recognition-based attendance system can be implemented on the Android platform using the Regula Forensics Face SDK. This technology has been proven to improve security and efficiency in Android attendance systems. In addition, this technology offers an accurate, fast, and secure biometric solution through flexible integration with Flutter. Despite technical and licensing limitations, this technology is still feasible for implementation in modern attendance systems.